Polarization insensitive switchable metamaterial absorber/reflector for X-band applications - M. G. Mustapha; M. K. A. Rahim; N. A. Murad; O. Ayop; S. Tuntrakool; M. A. Baba; A. Y. Iliyasu; Mohd Ezwan Jalil (Bulletin of Electrical Engineering and Informatics, 2020)
A unit cell of squared shaped polarization-insensitive switchable metamaterial absorber/reflector is presented. The structure operates at 10.20 GHz under both absorber mode and reflector mode configurations. Copper wire bridging the gaps to form a circular shape structure were used as switches for operation mode selections. The structure was designed on an FR4 substrate, and the incidental wave angles were varied from 0 to 50 degrees. The structure demonstrated almost 100% absorption at resonance, 3.314 GHz percentage bandwidth at 80% as an absorber. On the other hand, as reflector, it demonstrated almost a 90% reflection and a usable bandwidth of 3.327 GHz.